Livelihoods and welfare: Findings from the eighth round of the Myanmar Household Welfare Survey (October – December 2024) - Tauseef, Salauddin; Mahrt, Kristi; van Asselt, Joanna; Win, Hnin Ei (International Food Policy Research Institute, 2025)
The eighth round of the Myanmar Household Welfare Survey (MHWS), a nationally and regionally representative phone survey, was conducted between October and December 2024, with a recall period covering July to December. It builds on seven rounds implemented since December 2021. This report presents key findings on the livelihood and welfare dynamics during the second half of 2024.